Are Online Grocery Stores Being Designed to Support Consumer Nutrition Information Needs? Results from a Marketplace Survey (P04-151-19). (13th June 2019) - Olzenak, Kelly; Harnack, Lisa; Redden, Joeseph; French, Simone; Sherwood, Nancy
Abstract: Objectives: The aim of this study was to describe the availability of nutrition-related information and features on leading online grocery store websites. Methods: This study was a cross-sectional design. A systematic protocol was followed to assess availability of nutrition-related features on twelve online grocery shopping websites. The availability of nutrition facts panel and ingredient statement information for 26 food products across a variety of food categories was assessed along with the availability of additional nutrition-related features such as the ability to filter food search results by nutrition attributes. Means, frequencies, and percentages were calculated. Results: Common nutrition-related search filters available on the store websites included organic (10 of 12 stores), gluten free (nine of 12 stores), low in fat (six of 12 stores), and sugar-free/no sugar added (five of 12 stores). Nutrition facts panel information was available on the websites for 42%-100% of the packaged food and 33%-58% of the fresh produce items. Foods with available ingredient information ranged from 25%-100% for packaged foods to 50%-58% for the fresh produce items. Conclusions: Nutrition facts panel and ingredient statement information may be less available online for packaged foods than in physical stores where all packaged products must have labels. However, this information was sometimes available online for produce items even though labeling is not required on 'unpackaged' foods like fresh produce. Many online stores included nutrition-related features not available or feasible to provide in physical stores. Online grocery shopping marketplaces have the potential to support shoppers in making healthful food purchase decisions. Funding Sources: This research was supported by a University of Minnesota Division of Epidemiology and Community Health J.B. Hawley Research Award.